2007
DOI: 10.1002/prot.21800
|View full text |Cite
|
Sign up to set email alerts
|

Contact rearrangements form coupled networks from local motions in allosteric proteins

Abstract: Allosteric proteins bind an effector molecule at one site resulting in a functional change at a second site. We hypothesize that networks of contacts altered, formed, or broken are a significant contributor to allosteric communication in proteins. In this work, we identify which interactions change significantly between the residue-residue contact networks of two allosteric structures and then organize these changes into graphs. We perform the analysis on 15 pairs of allosteric structures with effector and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 52 publications
8
118
0
Order By: Relevance
“…Another study identified those conserved residues that had the largest contribution to maintaining short paths within the protein structure network; the results showed good agreement with experimental findings for 7 protein families [57]. For proteins undergoing a clear conformational change due to allostery, pairs of structures can be used to obtain an insight into the allosteric mechanism [93]. It was found that a communication pathway is best identified by combining the network of rigid substructures with the network of contact rearrangements [94].…”
Section: Allosteric Communication Pathways From Static Structuressupporting
confidence: 67%
See 1 more Smart Citation
“…Another study identified those conserved residues that had the largest contribution to maintaining short paths within the protein structure network; the results showed good agreement with experimental findings for 7 protein families [57]. For proteins undergoing a clear conformational change due to allostery, pairs of structures can be used to obtain an insight into the allosteric mechanism [93]. It was found that a communication pathway is best identified by combining the network of rigid substructures with the network of contact rearrangements [94].…”
Section: Allosteric Communication Pathways From Static Structuressupporting
confidence: 67%
“…• Network-based analysis of perturbation propagation is a fruitful method to identify intra-protein allosteric pathways [21,44,45,[59][60][61]71,93,97,102,111,127,208]. A successful candidate for the inter-protein allosteric pathways involved in allo-network drug action disturbs network perturbations specific to a disease state of the cell at a site distant from the original drug-binding site.…”
Section: Possible Methods To Identify Allo-network Drug Targetsmentioning
confidence: 99%
“…[51,54] Small-world allosteric networks and long-range communications in proteins appeared to be primarily governed by spatially separated clusters of specific functional residues. [55][56][57] These studies suggested that rapid transmission of allosteric interactions through small-world networks encoded in protein folds may have been a universal requirement encoded across diverse protein families.…”
Section: Structural and Network-based Models Of Allosteric Interactiomentioning
confidence: 97%
“…Some attempts have been made along these lines. Daily et al (23) analyzed networks of contact rearrangements to find regions of the protein proposed to transmit structural rearrangements between allosteric and active sites. Some attempts to use normal mode analysis to study relationships between residue mobility and allostery have been made (24,25), and Miyashita et al (26) attempted to estimate deformation energies of the elastic network model.…”
Section: Significancementioning
confidence: 99%